Thickness Effect on F8T2/C60 Bilayer Photovoltaic Devices - Natasha A. D. Yamamoto; Andreia G. Macedo; Lucimara S. Roman (Journal of Nanotechnology)
Copolymers based on fluorene-thiophene units have presented promising efficiencies in photovoltaic devices applications. They present good transport properties mainly after thermal treatment of the polymer films. Here, we investigate the properties of bilayer devices formed by the heterojunction of the polymer F8T2 with variable thickness and the fullerene. The series resistance of the equivalent circuit associated with the device increases as the polymer film gets thicker. The current-voltage characteristics of the bilayer devices follow the Mott-Gurney law of SCLC. For the best performing device we measured 2.1% of power conversion efficiency.